The Effectiveness of E-Learning Using Edmodo at Islamic Higher Education (PTKI) in East Kalimantan - Saugi, Wildan; Maesaroh, Dwi Titi (Southeast Asian Journal of Islamic Education, 2018)
A face to face instruction or lecture could not always be held for spontaneous activities such as a sudden meeting, faculty’s or institute’s activities or students’ activities which collide with the schedule. Teaching and learning activities become less effective since the lecture plans that have been set through the Semester Learning Plan could not run as planned and it influences the learning outcomes. Therefore, it needs an alternative solution that is utilizing e-learning using Edmodo because it is easy and familiar to use.This research is a pre-experimental design (non-design) using one-group pretest-posttest research design. The number of the samples was 76 students from IAIN Samarinda and STAI Sangatta. The instruments were pre-test, post-test, and questionnaires.The result of this research indicates that Edmodo based e-learning at PTKI in East Kalimantan is effective for the learning process. The two sample paired sign test towards pre-test and post-test shows that Z score is -7.330 with sig. of 0.000 and since sig. of 0.000 < 0.05, it means effective. In addition, the analysis towards questionnaires filled out by students show that Edmodo based e-learning at PTKI in East Kalimantan is effective for learning, with score percentage of 81.25% that has a very strong Score Interpretation Criteria.